Improving the status of social factors affecting health: a model for small and medium-sized enterprises to enter regional markets with an entrepreneurial marketing approach - Nesari , Tahereh; Namamian, Farshid; Hasani , Seyed Reza; Baghfalaki , Afshin (Social Determinants of Health, 2023)
Background: Many factors are effective in business development and experts have emphasized marketing and consider it one of the most important factors determining business survival. This study aimed to present a model of how small and medium companies enter regional markets with an entrepreneurial marketing approach. Methods: This study was a mixed research type. In the qualitative part of this study, market entry strategies were investigated and identified using the method of literature review and existing texts. To design the questionnaire, the opinions of 15 business management experts were used by the snowball method to obtain suitable samples for the study, and then the model was approved by the experts using the meta-heuristic method. Results: 100 people were present for the implementation of this study, 6.7% of the participants in the study had less than 10 years of work experience and 40% between 16 and 20 years, and 20% had more than 20 years of service. The proposed conceptual model of the research, which is obtained from the met heuristic process, shows that the initial conceptual model of the research consists of 4 categories of dimensions (entrepreneur orientation, market orientation, customer orientation, and innovation orientation) and 48 concepts and 182 codes (indicators). ConclusionGiven the importance of socioeconomic factors on health outcomes, businesses should consider the market distribution network, knowledge infrastructure, business capability, product innovation, the risk of participation, competitors, market development, and strategies.